2019
DOI: 10.1038/s41598-019-44933-6
|View full text |Cite
|
Sign up to set email alerts
|

Radiological assessment of effectiveness of soluble RAGE in attenuating Angiotensin II-induced LVH mouse model using in vivo 9.4T MRI

Abstract: We investigated the effectiveness of soluble Receptor for Advanced Glycation Endproducts (sRAGE) in attenuating angiotensin II (AngII)-induced left ventricular hypertrophy (LVH) using in vivo 9.4T cine-magnetic resonance imaging (CINE-MRI). Mice were divided into four groups: AngII (n = 9), saline (n = 10), sRAGE (n = 10), and AngII + sRAGE (n = 10). CINE-MRI was performed in each group after administration of the AngII or sRAGE, and CINE-MR images were analyzed to obtain parameters indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…In severe constriction, perfusion of organs distal to the band can be maintained through the Willis circle yet this again is not typical for aortic valve stenosis or hypertension. Continuous infusion of angiotensin II leads to systemic hypertension and holds major promise in improving our understanding of LV decompensation in pressure overload conditions and in the development of novel biomarkers and treatment strategies [27]. Indeed, in this study, we have demonstrated that reductions in ejection fraction associated with hypertension are more closely associated with the total burden of myocardial fibrosis than the degree of pressure afterload.…”
Section: Discussionmentioning
confidence: 60%
“…In severe constriction, perfusion of organs distal to the band can be maintained through the Willis circle yet this again is not typical for aortic valve stenosis or hypertension. Continuous infusion of angiotensin II leads to systemic hypertension and holds major promise in improving our understanding of LV decompensation in pressure overload conditions and in the development of novel biomarkers and treatment strategies [27]. Indeed, in this study, we have demonstrated that reductions in ejection fraction associated with hypertension are more closely associated with the total burden of myocardial fibrosis than the degree of pressure afterload.…”
Section: Discussionmentioning
confidence: 60%
“…PKCs-EKR1/2-NFκB-NLRP3-IL1β pathway signaling cascades have been shown to promote Ang II-induced cardiomyocyte hypertrophy in H9c2 cells through AT1 R, RAGE, and NADPH oxidase inhibition ( Lee et al, 2020 ). Soluble RAGE (sRAGE) was demonstrated as a decoy receptor for RAGE in Ang II-induced cardiomyocyte hypertrophy using in vivo and real-time 9.4T MR imaging ( Heo et al, 2019 ). In addition to RAGE, it has been noted that Toll-like receptor 2 (TLR2)- and TLR4-dependent pathways are stimulated by Ang II in cardiac dysfunction, fibrosis and hypertrophy ( Lee et al, 2020 ).…”
Section: Angiotensin II In Cardiovascular Systemmentioning
confidence: 99%
“…Standardly used 1.5 T and 3 T MRI allows visualization of myocardial pathologies including radiofrequency lesions “ in vivo ” ( Dickfeld et al, 2007 ) ( Badger et al, 2010 ) ( Markman and Saman 2017 ) ( Tofig et al, 2019 ) as well post-mortem. Moreover, high-resolution MRI systems are very promising and rapidly evolving imaging methods ( Schneider et al, 2008 ) ( Schneider et al, 2011 ) ( Wech et al, 2016 ) ( Ertürk et al, 2017 ) ( Erturk et al, 2019 ) ( Heo et al, 2019 ), which allow precise evaluation of the heart in unparalleled quality. Berte et al described the successful use of 1.5T MRI for in vivo imaging of the hearts and 9.4 T MRI (Bruker) for explanted hearts in 2015, where they used high-resolution MRI for evaluation of the lesions after radiofrequency (RF) ablation in an ovine experiment ( Berte et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%